Inclusion of sorghum (Sorghum bicolor (L). Moench) with protease and NSP-ase increases jejunal histomorphology and barrier function gene expression in broiler chickens - Lanti Yulianti Rebecca Sitohang; Ziyan A'fif Untari; Zuprizal Zuprizal; Muhsin Al Anas (Poultry Science)
ABSTRACT: The objective of this study was to investigate the effect of sorghum with or without protease and NSP-ase on performance, jejunal histomorphology, caecal short-chain fatty acids (SCFA), and gene expression of barrier function in the broiler chickens. A total of 240 males New Lohmann strain MB 202 broiler chicks (1-day-old) were randomly placed into 12 treatments with 4 replications, 5 birds per replicate for 35 d. The diets were a factorial combination of 3 levels of sorghum (0, 10, and 20%), 2 concentrations of protease (with and without protease), and 2 concentrations of NSP-ase (with and without NSP-ase). Results showed that villus height (VH) was improved (P < 0.05) and villus to crypt ratio (VH:CD) tended (P = 0.05) to increase with inclusion of sorghum. Inclusion of sorghum upregulated (P < 0.05) expression of the gene anti-inflammatory IL-13, and downregulated (P < 0.05) gene of toll receptor (TLR) (TLR-3 and TLR-4), pro-inflammatory (IL-18, IL-6, tumor necrosis factor-alpha (TNF-α) and tight junction zona occluding-1 (ZO-1). The result further indicated a decrease (P < 0.05) in the concentration of SCFA. The birds fed diets with protease had lower (P < 0.05) expression of gene TLR-4 and TLR-3, pro-inflammatory (IL-6 and TNF-α), and anti-inflammatory IL-10. Inclusion of sorghum markedly (P < 0.05) interacted with protease, increasing the total of SCFA, acetate, and VH in the broiler. The bird offered diets with NSP-ase had higher (P < 0.05) expression genes of pro-inflammatory IL-18 and TNF-α. Inclusion of sorghum and NSP-ase significantly (P < 0.05) interacted, upregulating gene of tight junction ZO-1 and anti-inflammatory IL-13 but downregulating gene TLR-3, and pro-inflammatory IL-6, while the SCFA production was decreased. Inclusion of sorghum in the diet with or without enzymes did not affect broiler performance (P > 0.05). In conclusion, a diet with sorghum improved jejunal histomorphology without negatively affecting growth performance. Additionally, supplementation with enzymes enhanced intestinal immune responses by up-regulating anti-inflammatory, and downregulating pro-inflammatory gene expression.